Predictors of distress in hospital physicians: protective and vulnerability factors - Martínez-Zaragoza, Fermín; Benavides-Gil, Gemma; Ato-García, Manuel; Solanes-Puchol, Ángel; Martín-del-Río, Beatriz; Fernández-Castro, Jordi; Pastor-Ruiz, Yolanda (Anales de Psicología / Annals of Psychology, 2014)
This study investigates the relationship between protective and vulnerability factors affecting health (distress) in medical staff. Participants were 127 doctors from four public hospitals, who were administered the Occupational Stress in Health Professionals Inventory, the Ways of Coping Questionnaire, the Maslach Burnout Inventory, the Symptom Checklist-90 Revised Questionnaire, and the Flow Trait Scale-2. Following the methodology of Partial Least Squares modeling (PLS), an explanation is given for distress in hospital physicians, where the avoidance coping strategy produces distress directly (B = .296) and indirectly (B = .139) through its influence on the increase of burnout (B = .314), which in turn is increased by occupational stress (B = .209). Professional flow, measured by professional efficacy and flow, acts as a good protector against distress (B = -.133), partly compensating the effects of the variables which have an increasing impact on an individual’s distress (GoF = .983). To sum up, when trying to predict a physician’s distress, four key elements should be considered: avoidance coping and its indirect effect through burnout on distress; the burnout construct itself and professional flow.